AUDIOLINGUAL METHOD; THEORY AND GUIDANCE FOR CLASSROOM PRACTICES - Sojuangon Rambe (English Education : English Journal for Teaching and Learning, 2013)
AbstractAudiolingual Method (ALM) emerged in 1950s on the shake of military purposes and its popularity declined in 1970s, criticized by linguists and practitioners in the aspect of language and learning theory as well as learning outcomes, together with the rise of communicative approach and other language teaching methods. The practice is still exist nowadays especially in teaching pronunciation, recorded materials and language labs.  In general, this method based on structural linguistics and psychological behaviorism; purposed to enable students to speak target language like native speakers do; develops oral communication through drills and repetition; teaches grammar inductively followed by filling gaps exercises; teaches new vocabulary through mimicry; puts listening and speaking in the top priority then develop reading and writing on spoken basis; and allows the further writing and translation in teaching students at advanced level. This paper discussed these features as guidance for teacher to teach English by using this method.  Key words: audio-lingual, aural-oral, drill, and repetition